Infinite horizon economies with borrowing constraints - Emma Moreno-García; Juan Pablo Torres-Martínez (Pontifícia Universidade Católica do Rio de Janeiro (PUC-Rio), Departamento de Economia, 2006)
We consider infinite horizon economies with incomplete financial markets. Securities are in positive net supply and may be infinite-lived. We establish existence of equilibria by requiring borrowing constrains instead of portfolio restrictions..
Keywords: 330; Equilibrium; Infinite horizon incomplete markets; Infinite-lived real assets.